Lichens and lichenicolous fungi of the Burguns`ka balka (Khersons`ka oblast) (CHORNOMORSKI BOTANICAL JOURNAL, 2009)
94species of lichensand lichenicolous fungi(43 genera, 22 families, 11 orders) are found in Burguns’ka balka raivne in southern Ukraine (Khersons`ka oblast / region). Acrocordia subglobosa(Vězda) Vězda & Poelt, Arthonia lecanorina(Almq.)R. Sant., Athelia arachnoidea(With.) J. R. Laundon, Collema fuscoviridis(With.) J. R. Laundon, Polycoccum marmoratum(Krempelh.) D. Hawksw. are revealed to be new to the steppe zone of Ukraine. 56 species (58,4%) are saxicolous occurring on limestone outcrops, 17 species (17,7%) are corticolous and and 17 species (17,7%) are lichenicolous. Three species (3,1%) are considered ubiquists with occurring on variety of substrats. The annotated list of taxa is compiled.
Keywords: biodiversity, calcicolous lichens, southern Ukraine, steppe zone.